Optical nonlinear dynamics in ZnS from femtosecond laser pulses - Yu-E Wu; Mengxin Ren; Zhenhua Wang; Wenhua Li; Qiang Wu; Sanming Yi; Xinzheng Zhang; Jingjun Xu (AIP Advances, 2014)
A wavelength swapping nondegenerate pump-probe technique to measure the magnitudes of the nonlinear optical dynamics as well as the relaxation time of electrons in high energy levels is presented using a ZnS single crystal wafer as an example. By pumping the sample with 800 nm femtosecond pulses and probing at 400 nm, nondegenerate two-photon absorption (N-2PA) happens exclusively, and the measured curves only show instantaneous features without relaxation tails. The N-2PA coefficient was derived explicitly as 7.52 cm/GW. Additionally, when the wavelengths of the pump and probe beams are swapped, extra information about the relaxation time of the hot electrons excited in the conduction band is obtained. The combined results above are helpful for evaluating the characteristics of an optical switches based on ZnS or other materials with respect to its nonlinear optical dynamic aspect.